Topographic Features of Five K-file Brands in Iranian Market: A Scanning Electron Microscopic Study - Shahravan, Arash; Gorjestani, Hedayat; Izadi, Arash; Mortazavi, Nazanin (Iranian Endodontic Journal, 2019)
Introduction: Endodontic files which are used to clean and shape the root canal space differ from each other regarding technical specifications. Recently, K-type files are repeatedly studied on their cutting efficiency. This study aims to evaluate the tip design and cutting efficiency of 5 brands of K-files, available in Iran dental market (naming Dentsply, Thomas, Mani, Perfect and Larmrose). Methods and Materials: In this descriptive study, topographic features of file tips were investigated by the scanning electron microscope (SEM). Those features included tip symmetry, tip design, tip angle, and the distance from the tip to the lowest flute. SEM images (×250 magnification) of files were prepared. Statistical tests (Fisher’s exact test, Chi-square, ANOVA, and t test) were used and P<0.05 was considered as significant. Results: Dentsply files had the most number of morphologically pyramidal sharp tips and the greatest tip angles. However, Larmrose files were the most frequent files having cutting sharp tips. Symmetrical tips existed among 100% of Dentsply and Mani brands. No significant differences were found with respect to distance from the file tip to the lowermost flute between different file brands of this study (P=0.2, One way ANOVA). Conclusion: Dentsply and Mani files possessed the most symmetrical tips and greatest tip angles. With respect to tip length, all 5 brands were satisfactory. However, neither of 5 brands evaluated topographically were outstanding in every aspect. Keywords: Endodontic K-files; Scanning Electron Microscopy; Topography